Investigation of Equivalent Unsprung Mass and Nonlinear Features of Electromagnetic Actuated Active Suspension - Jun Yin; Xinbo Chen; Jianqin Li; Lixin Wu (Shock and Vibration)
Electromagnetic actuated active suspension benefits active control and energy harvesting from vibration at the same time. However, the rotary type electromagnetic actuated active suspension introduces a significant extra mass on the unsprung mass due to the inertia of the rotating components of the actuator. The magnitude of the introduced unsprung mass is studied based on a gearbox type actuator and a ball screw type actuator. The geometry of the suspension and the actuator also influence the equivalent unsprung mass significantly. The suspension performance simulation or control logic derived should take this equivalent unsprung mass into account. Besides, an extra force should be compensated due to the nonlinear features of the suspension structure and it is studied. The active force of the actuator should compensate this extra force. The discovery of this paper provides a fundamental for evaluating the rotary type electromagnetic actuated active suspension performance and control strategy derived as well as controlling the electromagnetic actuated active suspension more precisely.